Exploring the Aquatic Plastisphere: Interactions of Plastic with Biofilm - Sakshi; Ranjan, Rajiv; Choudhary, Swati (Chronicle of Bioresource Management, 2024)
Microplastics have emerged as pollutants of concern in recent years due to their persistent nature and their adverse effects on living beings and the ecosystem. The ecosystem is significantly impacted by microplastics because of their tiny size, which makes it easy for them to enter food webs and biogeochemical cycles. In marine ecosystems, microorganisms primarily colonize plastic surfaces, where they can create biofilms, new biological niches for microbial communities, and form plastispheres. Plastic biofilm interactions affect the polymer’s physical and chemical properties, thereby leading to its degradation. In order to mitigate the annoyance of microplastic contamination, biofilms are being considered potential candidates for the remediation of marine environments. However, ongoing research in this field offers promising opportunities for developing innovative solutions to address plastic pollution.